2007
DOI: 10.1007/s11427-007-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the diploid gynogenetic hybrid clonal line of red crucian carp × common carp

Abstract: This study investigated the gynogenetic cytobiological behavior of the third gynogenetic generation (G(3)), which was generated from the diploid eggs produced by the second gynogenetic generation (G(2)) of red crucian carp x common carp, and determined the chromosomal numbers of G(3), G(2)xscatter scale carp and G(2)xallotetraploid hybrids of red crucian carp x common carp. The results showed that the diploid eggs of G(2) with 100 chromosomes, activated by UV-irradiated sperm from scatter scale carp and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…Our group has developed gynogenetic strains from natural origin red crucian carp, Carassius auratus cuvieri, goldfish, common carp, orange ornamental carp (Cyprinus carpio), grass carp, Erythroculter ilishaeformis, Xenocypris davidi Bleeker, and artificially cultivated strains including tetraploid hybrids of common carp with red crucian carp and tetraploid hybrids of red crucian carp with blunt snout bream [103][104][105][106][107]. We have developed gynogenetic strains of red crucian carp, Japanese crucian carp, and goldfish following activation using heterogenous sperms (M. amblycephala).…”
Section: Artificial Gynogenesis and Androgenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has developed gynogenetic strains from natural origin red crucian carp, Carassius auratus cuvieri, goldfish, common carp, orange ornamental carp (Cyprinus carpio), grass carp, Erythroculter ilishaeformis, Xenocypris davidi Bleeker, and artificially cultivated strains including tetraploid hybrids of common carp with red crucian carp and tetraploid hybrids of red crucian carp with blunt snout bream [103][104][105][106][107]. We have developed gynogenetic strains of red crucian carp, Japanese crucian carp, and goldfish following activation using heterogenous sperms (M. amblycephala).…”
Section: Artificial Gynogenesis and Androgenesismentioning
confidence: 99%
“…The survived fish that underwent the adversity were easy to obtain traits that resist harsh conditions. Liu et al [106] have obtained diploid gynogenetic offspring by using the diploid eggs from allotetraploid hybrids by gynogenesis without chromosome-doubling treatment. Through long-term research, we established a strain of diploid gynogenetic hybrids (G 1 -G 8 ) that were able to produce fertile diploid eggs.…”
Section: Artificial Gynogenesis and Androgenesismentioning
confidence: 99%
“…However, few fish can produce gynogenetic progenies, genetically identical or similar to the somatic cells of the mother, without any treatment for the doubling of chromosomes. This may be related to apomixis, premeiotic endoreduplication, or premeiotic endomitosis [Liu et al, 2007[Liu et al, , 2014Morishima et al, 2012;Arai and Fujimoto, 2013].…”
Section: Production Of Tetraploid Gynogenetic Loachmentioning
confidence: 99%
“…Interestingly, G 1 could also produce many diploid eggs, which could develop into the second gynogenetic diploid hybrid fish (G 2 ) without the treatment for doubling the chromosomes, then G 2 developed into G 3 in the same way. Based on the formation of diploid G 1 , G 2 and G 3 , a new diploid hybrid clonal line had been established [3] . In this study, we obtained tetraploids (A 1 -4n) and triploids (A 1 -3n) by mating males and females of A 0 , suggesting that A 0 could produce diploid gametes.…”
Section: The Advantages Of Androgenesis With Diploid Sperm and The Fomentioning
confidence: 99%
“…Then G 2 developed into G 3 in the same way. The formation of diploid G 1 , G 2 and G 3 indicated that a new diploid hybrid gynogenetic clonal line was established [3] . On the other hand, the diploid sperm produced by allotetraploid hybrids developed into diploid hybrid androgenetic fish (A 0 ) after the fertilization of the diploid sperm with the UV-treated eggs of goldfish, without the treatment for doubling the chromosomes.…”
mentioning
confidence: 99%